Pengaruh Gaya Kepemimpinan Transformasional dan Budaya Organisasi terhadap Motivasi Serta Dampaknya terhadap Kinerja Pegawai pada Badan Kepegawaian dan Pengembangan SDM Daerah Kabupaten Tanjung Jabung Timur - Alhudhori, M. (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the influence of transformational leadership style and organizational culture on motivation and its impact on employee performance at the Regional Personnel & Human Resources Development Agency of East Tanjung Jabung Regency using a sample of 78 respondents. The results of this research found that transformational leadership style and organizational culture have a significant effect on motivation. Transformational leadership style and work organizational culture together have a positive and significant effect on performance. Motivation has a positive and significant effect on performance at the Regional Personnel & Human Resources Development Agency of East Tanjung Jabung Regency